PELAKSANAAN PEMBANGUNAN KEPARIWISATAAN DAERAH BERBASIS BUDAYA DAN KEARIFAN LOKAL (Studi Di Kawasan Wisata Siring Sungai Martapura Kota Banjarmasin) - Mujahadah Mujahadah (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
Tourism is one of the highest foreign exchange earners. The importance of tourism development in each region will provide benefits such as bringing in foreign exchange from foreign tourists. Contributing to gross domestic product (GDP) and increasing regional original income (PAD) and employment will continue to increase. The realization of the implementation of regional tourism development based on culture and local wisdom requires the involvement of all parties, both Government, Private and Community which in its implementation is based on Banjarmasin City Regulation Number 28 of 2012 concerning Tourism and Regulations of the Mayor of Banjarmasin Number 25 of 2016 River Based Tourism Management and Development. This type of research used in this research is descriptive using a skinative approach. The data collection techniques are interviews, observation and documentation. The focus of this research is the Implementation of Regional Tourism Development in the Siring Sungai Martapura Tourism Area viewed from the Tourism Industry, Tourism Destinations, Marketing and Tourism Institutions.